Labour activism and organisational bricolage among Spanish and Italian emigrants in Germany - Castellani, S.; Roca, B. (Migrant organising: Community unionism, solidarity and bricolage, 2021)
This chapter explores labour organisation and collective action among Spaniards and Italians who migrated to Germany during the most recent economic recession (2008-2013). Even if the majority of the people who move freely within the EU were high educated and had a cosmopolitan profile, they massively entered the German secondary labour market. Moreover, when they claimed social and labour rights as EU citizens they faced increasing welfare chauvinism. Drawing on semi-structured interviews with activists and ethnographic observations of migrants’ organizations in Berlin, this study reflects on the processes of organisational bricolage. The authors show, first, how migrant workers creatively combined elements from different ethnic, national, and political traditions to develop innovative organisational forms, practices, and repertories of collective action. Second, they point out how they used these tools transnationally with existing trade unions and political organisations of countries of both origin and destination.